2020
DOI: 10.1111/ajr.12589
|View full text |Cite
|
Sign up to set email alerts
|

Using digital and social media for health promotion: A social marketing approach for addressing co‐morbid physical and mental health

Abstract: ObjectiveThis study examines consumer engagement with a social marketing digital media strategy designed to support the implementation of Equally Well—a program to improve the physical health of people living with mental illness.DesignA four‐stage strategic analysis and intervention mix were used as the theoretical framework to assess stakeholder needs and to evaluate the effectiveness of the intervention.SettingOnline and digital media.ParticipantsMental health consumers, carers, clinicians and service manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 24 publications
0
52
0
4
Order By: Relevance
“…In the design, there were qualitative and quantitative studies [15,16]. There were three systematic reviews and one thematic analysis that explored the better or worse of using social media among adolescents [20][21][22][23]. In addition, eight were cross-sectional studies and only three were longitudinal studies [24][25][26][27][28][29].The meta-analyses included studies published beyond the last five years in this population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the design, there were qualitative and quantitative studies [15,16]. There were three systematic reviews and one thematic analysis that explored the better or worse of using social media among adolescents [20][21][22][23]. In addition, eight were cross-sectional studies and only three were longitudinal studies [24][25][26][27][28][29].The meta-analyses included studies published beyond the last five years in this population.…”
Section: Resultsmentioning
confidence: 99%
“…The intimacy fun happens when social media promotes putting on a facade that highlights the fun and excitement but does not tell us much about where we are struggling in our daily lives at a deeper level [ 28 ]. Another study revealed that depression and time spent on Facebook by adolescents are positively correlated [ 22 ]. More importantly, symptoms of major depression have been found among the individuals who spent most of their time in online activities and performing image management on social networking sites [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…To date, co-design has proved successful in many contexts (Domegan et al, 2019; Mehmet et al, 2020), and differences between user-generated ideas and expert-generated ideas have been observed (Dietrich et al, 2016; Hurley et al, 2018). Benefits of co-design have been observed for researchers, users, and society at large (Slattery et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online advice forums and digital media could also be leveraged to provide a community of knowledge and support. 29 Such access to information and resources in an anonymous way has been found to facilitate identity development and self-acceptance of LGBTQI+ youth. 30 The appropriate promotional channels will be required to publicise such services using local mainstream and LGBTQI+specific channels of communication.…”
Section: The Individualmentioning
confidence: 99%
“…Telehealth services, for instance, could be leveraged to provide LGBTQI+ individuals with access to gay‐friendly specific services, without having to physically visit a local facility, or interact with local professionals; helping to protect their identity within their local rural community. Online advice forums and digital media could also be leveraged to provide a community of knowledge and support 29 . Such access to information and resources in an anonymous way has been found to facilitate identity development and self‐acceptance of LGBTQI+ youth 30 .…”
Section: Implications For Rural Service Provisionmentioning
confidence: 99%